EFEKTIVITAS PENERAPAN MALCOLM BALDRIGE CRITERIA DALAM PENINGKATAN PRODUKTIVITAS PT. PJB UP GRESIK - Abdurrahman Faris Indriya Himawan (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2018)
In this research has purposed for knowing the implementation of increasing productivity Malcolm Baldrige Criteria levels and the influence of increasing productivity in PT PJB UP Gresik. Malcolm Baldrige Criteria that is observed include Leadership, Strategic Planning, Costumer And Market Focus, Measurement Analysis And Knowledge Management, Human Resources Focus, Process Management And Business Result. The implementation of Malcolm Baldrige Criteria in PT PJB UP Gresik had been successes, in this case, it is indicated that has a good effectivness levels, it means that every criteria at Malcolm Baldrige has a good effevtivity of increasing productivity in PT PJB UP Gresik. The assessment of effetivness percentage is according to general by using Malcolm Baldrige Criteria is PT PJB UP Gresik showed the beginning of approach that is systematic in answering the backgrounds of regulations from every criteria items. But there is a big gap that is enough in approaching and deployment in some criterias. Based on the result of multiple linear regression analysis is found that influence of Malcolm Baldrige Criteria’s implementation in increasing productivity at PT PJB UP Gresik is according to the simultaneous has influenced that is significant whereas according to the partial only leadership criteria that has possitve influence in increasing productivity of PT PJB UP Gresik, another from that criteria does not have influence that is significant in increasing productivity at PT PJB UP Gresik.